The effect of social and personal norm on intention to patronize green hotels: extension of theory of planned behavior - Wang, Lei; Zhang, Qi; Ding, Yan-Yun; Wong, Philip Pong Weng* (Routledge, 2022)
Despite most previous studies investigated the relationship between consumers’ attitude and behavior gap by adopting the theory of planned behavior (TPB). However, patronizing green hotels is still considered to be one of the most persistent challenges in behavioral transformation agenda. This paper aims to contribute to the TPB by investigating the role of personal norm (PN) in explaining consumers’ intention to patronize green hotels. This study also argues that consumers’ social norms (SN) can influence their attitudes, perceived behavioral control (PBC) and PN toward intention, and attitude can influence their PBC. A total of 399 valid questionnaires were collected to empirically test the generated hypotheses using SPSS and AMOS. The findings indicated that SN positively influenced PN, attitude, PBC and intention, respectively. PN, attitude, and PBC were shown to positively influence intention. Furthermore, PN shown a mediating effect on the relationship between SN and intention, attitude displayed a mediating effect on the relationship between SN and intention, and PBC mediated the relationship between attitude and intention. This study expanded the TPB which incorporated PN as an antecedent to provide a better understanding on consumers’ intention to patronize green hotels. The theoretical contributions, practical implications and limitation are discussed accordingly.